Analisis Pembentukan MAT Pada Jaringan Sederhana Menggunakan Program Lazarus - Handayani, Esty; Sulistyorini, Rahayu; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Origin Destination Matrix (O-D MATRIX) is two- dimensional matrix are often to described thepatterns of movement that contains information the amount of intrazone movement. O-D MATRIXformation in this research on simple network with 5 origin-destination zone (O-D) used Gravitymethod with two-limitation . In this research, O-D MATRIX formation on a simple network usingLazarus program. Lazarus is the one of Integrated Development Environment (IDE) from FreePascal Compailer (FPC). FPC that can be used for Window, Linux, and MAC. If the previouscalculations requier a longer time, this program will be quickly and efficiently of O-D Matrix. Ittakes 3 hours to calculate O-D Matrix manualy and input the formula will enhance errorpossibility. This program spents 5 minutes to calculate O-D Matrix .Keywords: Lazarus, Origin Destination Matrix, Zone